Progressive deafness-dystonia due to SERAC1 mutations: a study of 67 cases - Maas, Roeltje R; Hörster, Friederike; Staufner, Christian (Annals of neurology, 2017)
Objective 3-Methylglutaconic aciduria, dystonia-deafness, hepatopathy, encephalopathy, Leigh-like syndrome (MEGDHEL) syndrome is caused by biallelic variants in SERAC1. Methods This multicenter study addressed the course of disease for each organ system. Metabolic, neuroradiological, and genetic findings are reported. Results Sixty-seven individuals (39 previously unreported) from 59 families were included (age range = 5 days-33.4 years, median age = 9 years). A total of 41 different SERAC1 variants were identified, including 20 that have not been reported before. With the exception of 2 families with a milder phenotype, all affected individuals showed a strikingly homogeneous phenotype and time course. Severe, reversible neonatal liver dysfunction and hypoglycemia were seen in >40% of all cases. Starting at a median age of 6 months, muscular hypotonia (91%) was seen, followed by progressive spasticity (82%, median onset = 15 months) and dystonia (82%, 18 months). The majority of affected individuals never learned to walk (68%). Seventy-nine percent suffered hearing loss, 58% never learned to speak, and nearly all had significant intellectual disability (88%). Magnetic resonance imaging features were accordingly homogenous, with bilateral basal ganglia involvement (98%); the characteristic “putaminal eye” was seen in 53%. The urinary marker 3-methylglutaconic aciduria was present in virtually all patients (98%). Supportive treatment focused on spasticity and drooling, and was effective in the individuals treated; hearing aids or cochlear implants did not improve communication skills. Interpretation MEGDHEL syndrome is a progressive deafness-dystonia syndrome with frequent and reversible neonatal liver involvement and a strikingly homogenous course of disease. Ann Neurol 2017;82:1004-1015
Gesehen am 13.07.2018